OS08.7.A Lomustine and the immunocytokine L19TNF are a promising treatment combination for recurrent glioblastoma. (5th September 2022) - Look, T; Puca, E; Stucchi, R; Luca, R; Roth, P; Neri, D; Weller, M; Hemmerle, T; Weiss, T
Abstract: Background: Treatment options for recurrent glioblastoma are limited and with the possible exception of regorafenib, no agent has demonstrated superior activity to lomustine. Therefore, there is an urgent need for more effective treatment strategies for recurrent glioblastoma. Here, we investigated different treatment combinations based on the tumor-stroma targeting antibody-cytokine fusion protein L19TNF in preclinical glioma models and translated the most effective treatment combination to patients with recurrent glioblastoma. Material and Methods: Orthotopic immunocompetent mouse glioma models were used to study the anti-glioma activity of L19TNF in combination with anti-PD1, bevacizumab or lomustine. Tumor growth was monitored by MRI. Flow cytometry and microscopy were used to characterize tumor-infiltrating-immune cells. MHC immunoaffinity purification and mass spectrometry were used to characterize the MHC immunopeptidome. Genetic mouse models were used to study immune-dependent effects. Subsequently, we translated the most efficient treatment combination to patients with recurrent glioblastoma within a phase I/II clinical trial (NCT04573192). Results: The combination of L19TNF and lomustine demonstrated strong synergistic anti-tumor activity in two immunocompetent orthotopic glioma models and cured a majority of tumor-bearing mice. In contrast, combinations with anti-PD-1 or bevacizumab had only limited anti-glioma activity. Furthermore, compared to the monotherapies, the combination of L19TNF and lomustine led to the strongest increase in tumor-infiltrating lymphoid cells as demonstrated by flow cytometry and microsopy and to the highest number of peptides presented in the context of MHC-I. The treatment effect was abrograted in different genetic immunodeficient mouse models. The treatment combination of L19TNF and lomustine was well tolerated in the first patients treated within a phase I/II clinical trial and we observed partial tumor responses also in patients with an unmethylated MGMT promoter. Conclusion: The combination of L19TNF and lomustine demonstrated promising anti-glioma activity and patients are currently recruited within a phase I/II clinical trial for patients with recurrent glioblastoma.